Differences in the Breastfeeding Babies Anthropometic Status Based on the Practice of Mothers Consuming Torbangun (Coleus Amboinicus Lour) Leaves in Toba Regency: PERBEDAAN STATUS ANTROPOMETRI BAYI BERDASARKAN PRAKTIK IBU MENYUSUI DALAM MENGKONSUMSI DAUN TORBANGUN (Coleus Amboinicus Lour) DI KABUPATEN TOBA - Serlina Silalahi; Ari Probandari; Sri Mulyani (Universitas Airlangga, 2023)
Torbangun leaves (coleus ambonicus lour) are a typical food in Toba Regency that can increase the secretion rate and volume of breast milk production. It is assumed that the existence of lactagogum can increase the achievement of breast milk coverage, but in contrast to the achievement of exclusive breastfeeding, it is still below the national target of 24.3% in Toba Regency.The purpose of this study was to analyze differences in the anthropometric status of breastfeeding babies based on the practice of mothers consuming and building in Toba Regency. The observational research method with a prospective cohort design with an observation time of two months with three anthropometric status measurements was carried out in May-July 2022. The research samples amounted to 226 people, divided into 2 groups, namely babies from mothers who consumed torbangun leaves and babies from mothers who did not consume. Determination of research samples with multistage random, data analysis using independent t-tests and mann-whitney tests. The results of the study did not have a difference in anthropometric status based on the z-score index WAZ (p=0.251), HAZ(p=0.305),WHZ(p=0.373) between babies from mothers who consumed torbangun leaves and babies from mothers who did not consume. Overall, the anthropometric status of the study subjects was between Z scores ≥-2 SD and ≤ 2 SD. It was concluded that there was no significant difference in anthropometric status based on the z-scores of WAZ, HAZ and WHZ.